Analisis Kepuasan Petani Dalam Pemanfaatan Limbah Panen Sayuran Didesa Lingga Kecamatan Simpang Empat Kabupaten Karo - Ruth Dameria Haloho; Chaula Lutfia Saragih; Fauzul Azhimah (Fakultas Pertanian, Universitas Timor, 2022)
Karo Regency is the largest horticultural production center in North Sumatra. In conducting outreach activities about the socialization of vegetable waste processing on agricultural land in Lingga Village, Simpang Empat District, Karo Regency, it is hoped that the extension workers can measure farmer satisfaction. This study aims to assess the level of farmer satisfaction with the socialization of vegetable waste processing on agricultural land. The analytical method used is the Job Description Index (JDI) job satisfaction analysis method by taking the entire population of the Arihta Ersada farmer group as many as 27 people. For farmer characteristics, multiple linear regression tests were carried out using the SPSS application. This study shows a very good assessment for each indicator set. The JDI indicator of this study was simultaneously very good as much as 43.8%, with a good rating of 34%, a poor satisfaction level of 12.3% and very bad 9.9%. While the partial of each indicator shows that this socialization is considered very good at 40.7%, the results of composting are 51.9%, income opportunities are 40.7%, the quality of socializers is 77.8%, farmer partners are 40.7%, and the condition of vegetable waste is 11.1%. The conclusion of this study shows that most of the farmers are very satisfied with the socialization of agricultural waste processing. Processing of agricultural waste is needed for fertilizer substitution, which has been a large cost opportunity and in the end is able to become a form of implementing organic agriculture.